Lower T Regulatory and Th17 Cell Populations Predicted by RT-PCR-Amplified FOXP3 and RORγt Genes Are Not Rare in Patients With Primary Immunodeficiency Diseases - Lee, Wen-I; Huang, Jing-Long; Lin, Syh-Jae; Yeh, Kuo-Wei; Chen, Li-Chen; Ou, Liang-Shiou; Yao, Tsung-Chieh; Jaing, Tang-Her; Shih, Ying-Fan; Wu, Chao-Yi (Frontiers in Immunology, 2020)
Deficiencies in T regulatory (Treg) and Th17 cells attenuate peripheral tolerance and the IL-17 family of cytokines, contributing to autoimmune disorders and opportunistic (fungal) infections, respectively. Because of limited blood samples from patients with primary immunodeficiency diseases (PIDs), a positive correlation/linear relationship between Treg and Th17 cells and their respective expressions of transcription factors forkhead box P3 (FOXP3) and retinoic acid-related orphan receptor γ (RORγt) by real-time PCR (RT-PCR) amplification was used to predict the percentages of Treg and Th17 cells in peripheral blood. Compared to glyceraldehyde 3-phosphate dehydrogenase (GAPDH) expression, the percentages of Treg and Th17 cells were calculated as the linear relationship to the 2-ΔCT value (cycle threshold). Among 91 PIDs patients, 68 and 78 had predicted Treg and Th17 percentages below 5% of the normal ranges (0.859 % and 0.734%, respectively), which expanded different categories beyond obvious T cell deficiency. Notably, FOXP3 was undetectable in one patient (CVID), RORγt was undetectable in four patients in six (one CVID, one CID, two neutropenia, one WAS, and one CMC), and both were undetectable in four patients (two SCID, one STAT1, and one periodic fever). In contrast, two patients with auto-IFNγ antibodies had increased susceptibility to intracellular mycobacterial infections, interrupted Th1 development and subsequently an elevation in Th17 cells. Both predicted Treg and Th17 percentages in the PIDs patients were more independent of age (months) than in the controls. The predicted Th17/Treg ratio in the PIDs patients overall was lower than that in the healthy controls (0.79±0.075 vs. 1.16±0.208; p=0.038). In conclusion, lower predicted Treg and Th17 cell populations calculated by RT-PCR-amplified FOXP3 and RORγt in PIDs patients at diagnosis can explain the higher potential phenotypes of autoimmune disorders and opportunistic infections, although effective interventions in the early stage might have prevented such phenotypic development and caused statistical bias in the comparisons.